Understanding intelligence in the twenty-first century : journeys in shadows - Scott, L. V. (Leonard Victor), 1957-; Jackson, Peter, 1964- (Studies in intelligence series., 2004)
This book examines critically the development of intelligence studies and assesses its contribution to the study of international relations. It draws upon the viewpoints of leading academics, journalists and former practitioners to explore the way.